Today’s Trends of Software Product Import-Substitution in Conditions of Economy Digitalization - I. E. Zhukovskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
Today software import-substitution in spheres and sectors of Russian economy is a priority trend in state programs being realized in the Russian Federation. The author analyzed governmental decisions concerning software import-substitution, studied software introduced in substituting foreign software at enterprises of Russian economy, showed its developers and prospects of its development. Apart from that, the article underlined that by 2025 according to state programs home-made software shall be used by organizations related to entities of critical information infrastructure such as banking sector, missile and space industry, military-industrial complex, nuclear and mining industry, public health service, science, iron-and-steel making and chemicals industry. At the same time import-substitution policy in general promotes upgrading of the payments balance structure, development of the academic sector and innovation technologies, growth in effective communication with developers of economic projects, where software is functioning, increase in the level and diversity of means and methods of information security, technological independence, population employment, cutting risks and raising competitiveness of industries and sectors of Russian economy. In line with numerous positive moments import-substitution policy demonstrates such drawback as closeness from some innovation of global economy. However, in conditions of sanctions the development of our own software, its efficient use in economic entities can provides cyber-security and technological independence.